Precarious Living: Assessing the disaster risk vulnerability of selected informal settlers in Dasmarinas City, Philippines - Aguilar, Maria Virginia (Harmoni Sosial: Jurnal Pendidikan IPS, 2021)
From the perspective of disaster management, the proliferation of slums and informal settlers poses a serious problem because their economic status inadvertently drives them to spaces unsuitable for housing. The informal settler often resides in areas prone to flooding, seismic activity, and landslides exposing them to a vicious repeat cycle of destruction and loss of life. Sitio Bato, a newly-formed informal settlers' community in Dasmarinas City, Philippines, is a case point. Situated near a creek and without electricity and water connection at the start of the study in 2019,  the residents are seemingly susceptible to disaster hazards. Against this backdrop, this study seeks to discuss the knowledge, attitudes, and practices of the residents of Sitio Bato regarding their vulnerability to disasters and the views of selected local government officials regarding the self-assessment of the informal settlers. Through the survey, a method using a questionnaire with household heads as respondents, and key informant interviews of local leaders, the following findings were notable in the study. First, the residents were knowledgeable of preventive mechanisms of floods, such as the important function of trees and the proper waste disposal techniques to exclude waterways. The barangay officials recognize the residents' neighborhood organization, and hence, their attendance to seminars/training on disaster management might have helped. Second,  in terms of attitude, it is innate for the informal settlers to care for their neighbors, and thus, it is part of their daily activity to check on each other's families. The lack of electricity encourages them to stay outdoors and talk to each other, strengthening their bond. Third, in terms of practice, trash disposal to the creek is not done, and hence, water from the creek flows without obstruction. A few Sitio Bato residents collect recyclable waste coming from communities in the upper part of the creek. Overall, residents do not see their living in Sitio Bato as precarious or hazardous. Local officials generally perceive the city's informal settlers as "privileged" because the services offered by the city government are received by everyone, regardless of the legality of their residence.